Impact of the coronavirus disease 2019 pandemic on stroke teleconsultations in Germany in the first half of 2020. (22nd March 2021) - Vollmuth, Christoph; Miljukov, Olga; Abu‐Mugheisib, Mazen; Angermaier, Anselm; Barlinn, Jessica; Busetto, Loraine; Grau, Armin J.; Guenther, Albrecht; Gumbinger, Christoph; Hubert, Nikolai; Hüttemann, Katrin; Klingner, Carsten; et al.
Abstract: Background and purpose: The effects of the coronavirus disease 2019 (COVID‐19) pandemic on telemedical care have not been described on a national level. Thus, we investigated the medical stroke treatment situation before, during, and after the first lockdown in Germany. Methods: In this nationwide, multicenter study, data from 14 telemedical networks including 31 network centers and 155 spoke hospitals covering large parts of Germany were analyzed regarding patients' characteristics, stroke type/severity, and acute stroke treatment. A survey focusing on potential shortcomings of in‐hospital and (telemedical) stroke care during the pandemic was conducted. Results: Between January 2018 and June 2020, 67, 033 telemedical consultations and 38, 895 telemedical stroke consultations were conducted. A significant decline of telemedical ( p < 0.001) and telemedical stroke consultations ( p < 0.001) during the lockdown in March/April 2020 and a reciprocal increase after relaxation of COVID‐19 measures in May/June 2020 were observed. Compared to 2018–2019, neither stroke patients' age ( p = 0.38), gender ( p = 0.44), nor severity of ischemic stroke ( p = 0.32) differed in March/April 2020. Whereas the proportion of ischemic stroke patients for whom endovascular treatment (14.3% vs. 14.6%; p = 0.85) was recommended remained stable, there was a nonsignificant trend toward a lower proportion of recommendation of intravenous thrombolysis during the lockdown (19.0% vs. 22.1%; p = 0.052). Despite the majority of participating network centers treating patients with COVID‐19, there were no relevant shortcomings reported regarding in‐hospital stroke treatment or telemedical stroke care. Conclusions: Telemedical stroke care in Germany was able to provide full service despite the COVID‐19 pandemic, but telemedical consultations declined abruptly during the lockdown period and normalized after relaxation of COVID‐19 measures in Germany. Abstract : Telemedical stroke care in Germany was able to provide full service despite the COVID‐19 pandemic, but telemedical consultations declined abruptly during the lockdown period and normalized after relaxation of COVID‐19 measures in Germany. Although the majority of the participating network centers treated COVID‐19 patients, relevant shortcomings regarding telemedical stroke care were not reported. Our representative nationwide study demonstrates the robustness of teleconsultation services in Germany during the COVID‐19 pandemic in the first half of 2020.